Husband's Support for the Childbirth Process: Concept Analysis - K, Heidi; Emin, Wan Sulastri; Taqiyah, Yusrah; Asnaniar, Waode Sri (PT.Mantaya Idea Batara, 2023)
It is hoped that the husband's support will make the mother feel calm so that the mother can face the delivery process smoothly. Lack of social support from the husband is a significant determinant of depression in childbirth. The purpose of conducting a conceptual analysis of a husband's help, in the beginning, is to find out how much the benefits or effects of a husband's support during childbirth are. The method used in this concept analysis refers to the technique developed by Walker & Avant using the PubMed and Scopus databases both domestically and abroad. The process of conceptual analysis goes through the stages of choosing a concept, determining goals, identifying the use of the idea, determining attributes, creating a case model, making borderline and contrary cases, identifying antecedents and consequences and determining empirical references. Husband's physical and psychological support, as well as support in undergoing childbirth, has a positive impact in reducing anxiety and labour pain to complications of labour and postpart